Aerobic in water is better than aerobic on land in the treatment of overweight teenage women - Gian Lisuari Adityasiwi; Yoga Handita; Marti Rustanti (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Having a beautiful body is a teenage woman’s dream, but those who are overweight have difficulty losing weight because of an imbalance between energy intake and energy use. To prove that aerobics in water is better than aerobics on the land to lose weight teenage women. Methods: We included overweight teenage overweight women. The research design used randomized pre and post-test designs. The research subjects were 22 overweight teenage women 18 – 21 years old and divided into two groups. Subjects get treatment three times a week for eight weeks. The first group received aerobics in water, and the second group received aerobics on land. The body weight measurement using Camry scales. Result: Based on the resulting test for aerobic in water, the p= 0.01, and the result for aerobic in land p= 0.624. Aerobic in water values with p<0.05, which states that aerobic in water has a significant effect on weight loss. However, aerobics on land results in a p> 0.05, meaning that it is not significant for weight loss. Conclusion: Aerobic in water is more effective than aerobic on the land to lose weight for teenage women.